Implementasi Cash Management System dalam Meningkatkan Efisiensi dan Transparansi Pengelolaan Kas pada Industri Manufaktur: Studi Kasus PT Cahaya Sejati Metal Sebagai Pengguna Kopra by Mandiri - Tasya, Mutiara Septiani; Thoha, Muarif; Wardana, Muhammad Rezky; Achsan, Harry Tursulistyono Yani (CV. Strata Persada Academia, 2024)
When facilitating transparent cash management, deploying the Cash Management System (CMS) is practical and efficient. Through a qualitative descriptive case study approach, this research seeks to understand the function that CMS Kopra by Mandiri plays in the management of cash at PT Cahaya Sejati Metal. The data for this study comes from a review of the relevant literature, interviews, and observations. Even though the change from authorization that was previously dependent on hardware to approval that is based on smartphone applications creates obstacles, the findings provide evidence that CMS has the potential to improve the effectiveness and transparency of cash management. It is necessary to provide user training, technical support, and security assurances to fulfill the requirements for a successful transition.